Indonesia's Commercial Diplomacy towards South Korea in Efforts to Realize EV Battery Project Investment - Nadhif, Aulia; Suryadipura, Dadan (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
The EV battery project in Indonesia is one of Indonesia's nickel downstream policy agendas. This policy aims to be able to increase the value of nickel commodities and create Indonesia's ability to be able to engage in the downstream industry. To realize the EV battery project, the Indonesian government is cooperating with South Korea in developing the EV battery industry in Indonesia. This article focuses on the commercial diplomacy efforts of the Indonesian government to obtain investment for developing the EV battery industry in Indonesia through investment promotion. This article uses qualitative research methods. After conducting an analysis, this article shows that the Indonesian government is carrying out commercial diplomacy activities by using IIPC Seoul as an extension of the Ministry of Investment/BKPM which acts as a facilitator and clearing agent to facilitate investment from South Korea and Indonesia. This effort is assisted by other government agencies such as the Ministry of BUMN, Ministry of Energy and Mineral Resources, and others to achieve a large investment score for the development of the EV industry in Indonesia. This article concludes that the commercial diplomacy carried out by the Indonesian government succeeded in achieving the goal of obtaining investment for the EV battery project to be able to increase the value of nickel commodities and create a downstream industry. Keywords: Commercial Diplomacy, Nickel Downstream, Indonesia, Investment Promotion, EV Battery Proyek baterai EV di Indonesia merupakan salah satu agenda dalam kebijakan hilirisasi nikel di Indonesia. Kebijakan ini bertujuan untuk dapat meningkatkan nilai komoditas nikel dan menciptakan kemampuan Indonesia untuk dapat bergerak dalam industri hilirisasi. Untuk dapat merealisasikan proyek baterai EV, pemerintah Indonesia melakukan kerja sama investasi terhadap Korea Selatan untuk dapat mengembangkan industri baterai EV di Indonesia. Artikel ini fokus kepada usaha perkembangan industri baterai EV di Indonesia melalui promosi investasi. Artikel ini menggunakan metode penelitian kualitatif. Setelah melakukan analisis, artikel ini menunjukkan bahwa pemerintah Indonesia melakukan aktivitas diplomasi komersial dengan menggunakan IIPC Seoul sebagai perpanjangan tangan dari Kementerian Investasi/BKPM yang bertindak sebagai fasilitator serta clearing agent untuk dapat memudahkan lajur investasi dari Korea Selatan dan Indonesia. Usaha ini dibantu dengan perangkat pemerintah lainnya seperti Kementerian BUMN, Kementerian ESDM dan lainnya sehingga dapat mencapai torehan investasi yang besar untuk pengembangan industri EV di Indonesia. Artikel ini menyimpulkan bahwa diplomasi komersial yang dilakukan pemerintah Indonesia berhasil mencapai tujuan yaitu mendapatkan investasi untuk proyek baterai EV untuk meningkatkan nilai komoditas nikel dan menciptakan industri hilirisasi. Kata-kata kunci: Diplomasi Komersial, Hilirisasi Nikel, Indonesia, Promosi Investasi, Proyek Baterai EV